Analysis of the Principal's Quality Leadership on the Teacher's Work Commitment - Budi Santoso; Nani Imaniyati; Try Hikmawan; Lia Rostini (Indonesian Journal of Multidiciplinary Research, 2023)
This study aims to describe the level of quality leadership effectiveness of the principal, the level of the teacher work commitment, and to find out whether there is an effect of the principal's quality leadership on teacher work commitment. The research method uses explanatory surveys. The technique of collecting data using a questionnaire. The respondents were 105 teachers. The data analysis technique uses simple regression. The results showed that the principal's quality leadership had a significant and significant influence on the teacher's work commitment. Thus, the teacher's work commitment can be increased through Increasing Principal Leadership.